Overview of research on virus-resistant breeding of melon - Tian, Shoubo; Diao, Qiannan; Cao, Yanyan; Yao, Dongwei; Zhang, Wenxian; Zhang, Hui; Du, Xuan; Zhang, Yongping (Frontiers in Plant Science, 2024)
Virus-resistant breeding of melon is of crucial significance in modern agriculture. The development of virus-resistant melon varieties not only poses challenges in balancing melon quality and resistance but also contributes to sustainable agricultural development. This research focuses on the exploration and application of various breeding techniques to enhance the virus resistance of melon varieties. Molecular markers associated with virus resistance genes have been identified and utilized in marker-assisted selection, enabling more efficient and targeted breeding. Genetic engineering approaches have also shown promise, introducing specific resistance genes into melon genomes. In addition, traditional breeding methods, such as hybridization and selection, continue to play an important role in creating virus-resistant melon lines. The development of virus-resistant melon varieties not only contributes to sustainable agricultural development but also poses challenges in balancing melon quality and resistance. The combination of these approaches holds great potential for developing melon varieties with improved virus resistance, thereby increasing yield and quality, and reducing the economic losses caused by viral infections in melon production.